2018
DOI: 10.1039/c7cp07267h
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of single protein explosions induced by X-ray lasers

Abstract: Single particle imaging (SPI) using X-ray pulses has become increasingly attainable with the advent of high-intensity free electron lasers. Eliminating the need for crystallized samples enables structural studies of molecules previously inaccessible by conventional crystallography. While this emerging technique already demonstrates substantial promise, some obstacles need to be overcome before SPI can reach its full potential. One such problem is determining the spatial orientation of the sample at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…In an earlier study we described the trajectories of the ions from a protein exploding due to the heavy ionization caused by an XFEL pulse. 13 There it was shown that the same ions from individual explosions tend to fly out in similar directions. This suggests that recording the paths of the ejected ions could be a way to determine the orientation of the protein at the moment when it is hit by the XFEL pulse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study we described the trajectories of the ions from a protein exploding due to the heavy ionization caused by an XFEL pulse. 13 There it was shown that the same ions from individual explosions tend to fly out in similar directions. This suggests that recording the paths of the ejected ions could be a way to determine the orientation of the protein at the moment when it is hit by the XFEL pulse.…”
Section: Methodsmentioning
confidence: 99%
“… 21 It has also been shown at the same time that encapsulating biomolecules in water will lead to a reduction of radiation damage, 22 and furthermore the Coulomb explosion of single molecules becomes more reproducible when the samples are slightly hydrated. 13 …”
mentioning
confidence: 99%
“…It has recently been shown that the random orientation and the low photon signal per shot can be tackled with de novo correlation approaches and that a low number of coherently scattered photons are sufficient 35 . Recent studies discuss ways to experimentally preorient a protein before the X-ray exposure, 36 or orient the sample postexposure 8 . The present study does not address the problem with finding the orientation of the sample as it is hit by the XFEL pulse but investigates the impact of damage on the diffraction patterns from aligned molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Following our earlier work, 8,19,20 we simulated the interaction between a lysozyme protein molecule (PDB identifier 1LYS 21 ) and an ultrashort XFEL pulse using the molecular dynamics (MD) software GROMACS 3 22 . MD is a simulation scheme based entirely upon classical mechanics that has been shown to accurately describe such interactions 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation